Occupational Protein Contact Dermatitis: Two Case Reports - Joana Rocha; Teresa Pereira; Artur Sousa-Basto; Celeste Brito (Case Reports in Medicine)
Protein contact dermatitis (PCD) is a contact dermatitis caused by high-molecular-weight proteins. This entity has been reported with increasing frequency, most commonly as occupational hand dermatitis in food handlers. Clinically, it is characterized by a chronic and recurrent dermatitis with erythema, scaling, and fissures with acute exacerbations occurring a few minutes after contact with offending allergen. We report two cases in confectioners who presented with chronic hand dermatitis.